Analisis Determinan Kualitas Audit Kantor Akuntan Publik (KAP) Kota Semarang - Diana Puspitasari; Yeni Kuntari; Triani Triani (Jurnal Ilmiah Aset, 2023)
The purpose of this study was to determine and analyze the factors that affect audit quality which include audit tenure, audit fee, professional ethics, and auditor competence on audit quality in Public Accounting Firms (KAP) Semarang City. The method used in this research was a survey using a questionnaire. The population and sample of this study were all auditors in Public Accounting Firms (KAP) Semarang City, totaling 80 auditors. The sampling technique used was saturated sampling, where all members of the population are used as research samples. The analytical tool used in this research was multiple regression analysis. Based on the results of data processing, it can be concluded that: Audit tenure and audit fee had a significant effect on audit quality, while professional ethics and auditor competence had no significant effect on audit quality.